PENGARUH KINERJA KEUANGAN TERHADAP PERUBAHAN HARGA SAHAM BANK UMUM SYARIAH NASIONAL DI BURSA EFEK INDONESIA (Studi Kasus: PT Bank Panin Dubai Syariah, Tbk.) - Benny Barnas (Jurusan Akuntansi Politeknik Negeri Bandung, 2019)
Abstract: The purpose of this research is to examine the effect of Financial Performance, namely Return on Assets (ROA) and Earnings Per Share (EPS) on the stock price’s changes of National Sharia Commercial Banks are listed on the Indonesia Stock Exchange (IDX). The research hypothesis was analyzed using multiple linear regression methods, while the financial data is taken from Bank Panin Dubai Syariah, Tbk. with the period of 2014-2017. The results indicate that Return on Assets (ROA) and Earnings per Share (EPS) both partially and simultaneously influence on stock prices. However, the result of adjusted R2 show that 38,30 percent of stock prices are influenced by the Return on Assets (ROA) and Earning per Share (EPS), while 87,90 percent is influenced by other variables outside this model. Keywords: Return on Asset (ROA), Earning per Share (EPS), and Price of Share.